The Cooperative Learning Method in Teaching EFL to Armenian Students - Markaryan, Arus; Avakyan, Naira (Armenian Folia Anglistika, 2012)
The article addresses certain advantages and drawbacks of the cooperative learning method, as well as the skills obtained by learners through the application of this method. Due to a number of features, the method may especially be of great use for developing communication skills in a foreign language. The authors of the article suggest certain types of revision of the material, homework checking and topic discussion that might be of interest and help for learners.